Durian albedo and eggshell-based smart edible film with infused butterfly pea flower extract as active agent - Ignasius Radix Astadi Praptono Jati; Adrianus Rulianto Utomo; Erni Setijawaty; Rachel Meiliawati Yoshari; Tarsisius Dwi Wibawa Budianta; Thomas Indarto Putut Suseno; Fitriyono Ayustaningwarno (Discover Food)
Abstract The aims of this research are to investigate the effects of different concentrations of butterfly pea flower extract infusion as an active agent on the properties of durian fruit albedo and eggshell-based smart edible films. The butterfly pea flower was extracted using water with the ratios of 1:50 (T1), 1:100 (T2), 1:150 (T3), 1:200 (T4), 1:250 (T5), and 1:300 (T6) (w/v). The film was formulated using durian albedo, eggshell, sorbitol, and cornstarch, which was mixed with butterfly pea flower extract and mold using the casting method. The analysis performed included anthocyanin and phenolic content, antioxidant activity, tensile strength, elongation, water vapor transmission rate, scanning electron microscopy, Fourier transform infrared spectroscopy, and smart indicator examination using fresh milk model system. Different concentrations of butterfly pea extract affect the physicochemical properties of smart edible film. The increase in extract concentration increased anthocyanin and phenolic contents, which align with the increase in antioxidant activity. Meanwhile, the presence of bioactive compounds in the formulation reduced the tensile strength of the film and increased its elongation, as confirmed by SEM and FTIR results. Smart edible film can act as an indicator in the fresh milk model by changing color according to the change in pH due to milk spoilage.